Islamisasi Pengetahuan dan Model Pengembangannya pada Madrasah - Mukhibat Mukhibat (Nadwa: Jurnal Pendidikan Islam, 2013)
Madrasah in Indonesia have exciting development because of its integration with modernity and political support of the state that aligned with the public schools. However, it is recognized that the model of madrasah education in the country's legislation, led to dualism education system in Indonesia, which has not been resolved until now. The problem is a challenge in realizing the ideal madrasah. Through a historical-philosophical approach, this study examines the redefinition of the Islamization of knowledge by tracing historically the initial idea of Islamization of knowledge in responding to the challenges facing the madrasah. Through critical analysis examines the implications of the redefinition of the Islamization of knowledge and development models at themadrasah. There are at least three models of Islamization of knowledge that can be developed in the development and empowerment of the madrasah, the purification of the model, the model of modernization, and the model of Islamic neo-modernism. AbstrakMadrasah di Indonesia mengalami perkembangan menarik karena integrasinya dengan modernitas serta dukungan politik negara sehingga sejajar dengan sekolah umum. Namun  demikian, diakui bahwa model pendidikan madrasah di dalam perundang-undangan negara, memunculkan dualisme sistem pendidikan di Indonesia yang belum dapat diselesaikan hingga sekarang. Problem tersebut menjadi tantangan tersendiri dalam mewujudkan madrasah yang ideal. Melalui pendekatan historis-filosofis, penelitian ini mengkaji tentang redefinisi Islamisasipengetahuan dengan melakukan penelusuran historis terhadap gagasan awal Islamisasi, dalam merespons tantangan yang dihadapi madrasah. Melalui analisis kritis tersebut dikaji implikasi redefinisi Islamisasi pengetahuan dan modelpengembangannya pada madrasah. Setidaknya ada tiga model Islamisasi pengetahuan  yang  dapat  dikembangkan  dalam  pengembangan  dan pemberdayaan madrasah, yaitu model purifikasi, model modernisasi, dan model neo-modernisme Islam.